Proposal of a didactic strategy for the development of communicative competence based on SWOT analysis. - Vargas López, Helen Sofia; Quiroz Brenes, Jennifer Lisseth; Mendoza García, Jesly Milena; Pavón López, Joel Andrés; Pérez Quiroz, Mellany Clara (Torreon Universitario Magazine, 2025)
The research was carried out using the SWOT analysis methodology to observe and analyze the application of the Language and Literature curriculum in Secondary Education at the Maestro Gabriel Institute, located in the department of Managua, Nicaragua. The study was realized in the classroom, where teachers, students and parents participate, and was based on the management of the language and literature curriculum, its relationship with the National Plan to Fight Poverty (PNLCP), communicative competence in Language and Literature and strategies for improving the Language and Literature curriculum. The vision and mission of the Ministry of Education (MINED) was presented and then the data was analyzed according to the SWOT methodology. Subsequently, strategic objectives were presented with their respective strategies and goals for improving the curriculum based on the analysis carried out previously. Finally, a strategic support plan was presented, which contains goals and actions that help improve the teaching-learning process.